Identification Guide to the Fossil Plants of the Horseshoe Canyon Formation of Drumheller, Alberta. - Aulenback, Kevin R., 1960- (University Of Calgary Press, 2009)
Plant fossils have helped scientists reconstruct the natural surroundings that supported the growth and evolution of dinosaurs - their food sources and habitat. While there are many scientific and general books on the dinosaurs and dinosaur fossils of the Horseshoe Canyon Formation, this is the first general publication on fossil plants within the province of Alberta since 1949. The information in this guide is based on Kevin Aulenback's years of experience and discovery with hands-on investigation of fossil plants in the Horseshoe Canyon Formation and other areas, and it is supported with the most up-to-date scientific discussion on paleobotany (the study of ancient plants) and palynology (the study of spores and pollen). Identification Guide to the Fossil Plants of the Horseshoe Canyon Formation of Drumheller, Alberta is an easy-to-use guide for the amateur and professional alike to identifying Cretaceous fossil plant finds. Illustrated with over 800 drawings and photographs, the guide gives the reader/collector enough information on their finds, as well as on still-living comparatives, to accurately identify fossils within the field or lab. The guide contains many unpublished fossil finds noted by the author over sixteen years of research, discovery, and observation in the Horseshoe Canyon Formation.